Increasing labor mobility as factor reduce the level of youth unemployment - Kuchyn, Sergei Pavlovich; Harapko, Maryna Ivanivna (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
In the article the modern problem of unemployment is investigated among young people. An accent is done on the factor of increase of labour mobility for reduction of unemployment rate among young people. The list of measures is offered on the improvement of situation in the spheres of youth employment.